2021
DOI: 10.3389/fmars.2020.539646
|View full text |Cite
|
Sign up to set email alerts
|

Severe Flooding in the Atoll Nations of Tuvalu and Kiribati Triggered by a Distant Tropical Cyclone Pam

Abstract: Tropical cyclone (TC) Pam formed in the central south Pacific in early March 2015. It reached a category 5 severity and made landfall or otherwise directly impacted several islands in Vanuatu, causing widespread damage and loss of life. It then moved along a southerly track between Fiji and New Caledonia, generating wind-waves of up to approximately 15 m, before exiting the region around March 15th. The resulting swell propagated throughout the central Pacific, causing flooding and damage to communities in Tuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Future work could include the effect of waves on extreme sea levels for open ocean sandy beaches 39 – 41 and reef environments 42 along with the future nonstationary changes to EVD from global climate model projections 24 . Future work could also replace the sea level residual with skew surge analysis which could be recombined with tide using convolution methods 43 along with structural function approaches 41 to define extreme water level populations.…”
Section: Discussionmentioning
confidence: 99%
“…Future work could include the effect of waves on extreme sea levels for open ocean sandy beaches 39 – 41 and reef environments 42 along with the future nonstationary changes to EVD from global climate model projections 24 . Future work could also replace the sea level residual with skew surge analysis which could be recombined with tide using convolution methods 43 along with structural function approaches 41 to define extreme water level populations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ranasinghe et al [45] and Anderson et al [46] observed shoreline rotation at embayed beaches, and Trombetta et al [47] observed an alongshore sediment drift reversal with large consequences for coastal zone management and infrastructures. These remote swells can also drive dramatic overtopping [6] even at storm-free areas, such as in the Gulf of Guinea [1,48], facing the South Atlantic storm track, and in the Pacific due to distant tropical cyclones [17,[49][50][51].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For some locations, TCs making landfall nearby are most important (e.g., Charchenga), while for other locations extreme tracks passing at larger distance are equally important (e.g., Batticaloa). For example, TC generated swell waves have caused flooding at small islands in the Pacific over 1000 km away from the TC-track (Hoeke et al, 2020). In these environments, even for the SLMPS configuration, it is recommended to use a large selection domain that covers a wide range of tracks.…”
Section: Optimal Configurationmentioning
confidence: 99%